The PsbH protein is associated with the inner antenna CP47 and facilitates D1 processing and incorporation into PSII in the cyanobacterium Synechocystis PCC 6803 - Komenda, Josef; Tichý, Martin; Eichacker, Lutz A (Plant & cell physiology, 2005)
Analysis of a number of PSII complexes detectable in the wild-type and mutant cells of the cyanobacterium Synechocystis sp. PCC 6803 showed that the PsbH protein is present in the complexes containing CP47, including unassembled CP47. In a mutant lacking CP47, in which the PSII assembly is stopped at the level of the D1-D2-cytochrome b-559 reaction centre complex, a negligible amount of the PsbH protein was not bound to this complex but was detected in the free form. The results indicate that the PsbH protein has a high affinity for CP47 and during PSII assembly most probably first associates with CP47 and this pair is subsequently attached to the reaction centre complex. Similarly to CP47, the PsbH protein exhibits a slow light-induced degradation in the presence of protein synthesis inhibitor. The absence of the PsbH protein leads to a greatly increased D1 pool that is not associated with other PSII proteins or it is present as a part of the reaction centre complex. We conclude that PsbH is important for the prompt incorporation of the newly synthesized D1 protein into PSII complexes and for the fast D1 maturation.
Keywords: Photosystem II Protein Complex; světlo; Synechocystis; Isoelectric Focusing; Light-Harvesting Protein Complexes; Electrophoresis, Polyacrylamide Gel; fosfoproteiny; světlosběrné proteinové komplexy; Light; Phosphoproteins; isoelektrická fokusace; elektroforéza v polyakrylamidovém gelu; fotosystém II (proteinový komplex)